Development of heterogeneous base catalyst and the optimization of the transesterification of Jatropha curcas oil into biodiesel - Piecco, Kurt Waldo E. Sy
Environmental pollution and the ever increasing prices of petroleum products have motivated the search and development of cleaner and renewable alternative fuels, like biodiesel. To reduce the cost of biodiesel production, Jatropha curcas oil may be used as feedstock. The use heterogeneous catalysts may also reduce the cost further and minimize pollution.